The Effect of Microteaching Lectures in Improving Nine Basic Teaching Skills for University Students - Wulandari, Viona Dwi; Wirdati, Wirdati (STIT Ahlussunnah Bukittinggi, 2024)
The microteaching course is a course that is obligated to students of the Islamic Religious Education study program at Universitas Negeri Padang. This course aims to train students to master basic teaching skills while implementing them in the classroom. This research aims to analyze whether the microteaching course is effective to improve students' ability to master nine basic teaching skills before and after taking the microteaching course. This research uses quantitative methods with a correlational approach. Data sources were taken from active students of the Islamic Religious Education study program at Universitas Negeri Padang batch 2020. All research data was processed statistically using quantitative analysis software IBM SPSS Version 29 For Mac. The results of the analysis show that the microteaching course is effective in improving the ability of Islamic Religious Education students to master nine basic teaching skills before and after taking the microteaching course according to student perceptions. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.